Voclosporin as a Treatment for Noninfectious Uveitis. (January 2013) - Schultz, Clyde
Voclosporin is a relatively new calcineurin inhibitor that has been used successfully in humans for the treatment of plaque psoriasis. Available data indicate a good safety profile for this treatment and a significant increase in quality of life for psoriasis patients. More recently, voclosporin has been used to treat ophthalmic conditions such as uveitis. The limited data available indicate at least comparable results relative to current therapy with a better safety profile. Here, we analyze data from human and animal studies and the mode of action of voclosporin. Available safety profile data are also discussed.